Verification of DES for flow over rigidly and elastically-mounted circular cylinders in normal and yawed flow. (April 2020) - Wu, Xingeng; Jafari, Mohammad; Sarkar, Partha; Sharma, Anupam
Abstract: A computational approach based on a k - ω delayed detached eddy simulation model for predicting aerodynamic loads on a smooth circular cylinder is verified against experiments. Comparisons with experiments are performed for flow over a rigidly-mounted (static) cylinder and for an elastically-mounted rigid cylinder oscillating in the transverse direction due to vortex-induced vibration (VIV). For the static cases, measurement data from the literature is used to validate the predictions for normally-incident flow. New experiments are conducted as a part of this study for yawed flow, where the cylinder axis is inclined with respect to the inflow velocity at the desired yaw angle, β = 3 0 ∘ . Good agreement is observed between the predictions and measurements for mean and rms surface pressure. Three yawed flow cases ( β = 1 5 ∘, 3 0 ∘, & 4 5 ∘ ) are simulated and the results are found to be independent of β (independence principle) when the flow speed normal to the cylinder axis is selected as the reference velocity scale. Dynamic (VIV) simulations for an elastically-mounted rigid cylinder are performed by coupling the flow solver with a solid dynamics solver where the cylinder motion is modeled as a mass–spring–damper system. The simulations accurately predict the displacement amplitude and unsteady loading over a wide range of reduced velocity, including the region where "lock-in" (synchronization) occurs. VIV simulations are performed at two yaw angles, β = 0 ∘ and 45° and the independence principle is found to be valid over the range of reduced velocities tested with a slightly higher discrepancy when the vortex shedding frequency is close to the natural frequency of the system.